CDX2 Expression in Gastric Carcinoma: A Clinicopathological Study - Halder, Aniket; Kundu, Mousumi; Das, Ram Narayan; Chatterjee, Uttara; Datta, Chhanda; Choudhuri, Manoj Kr; Chatterjee, Bitan (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Gastric cancer accounts for 7.8% of cancers worldwide and adenocarcinoma is the commonest histological type. Both gastric and intestinal phenotypic cell markers are expressed in gastric carcinomas. CDX2 is an intestinal transcription factor, which can be demonstrated in intestinal metaplasia and gastric carcinomas of the intestinal type. Unlike colorectal carcinomas, the role of CDX2 in gastric carcinomas as a prognostic variable is yet to be established. Ki-67 is a transcription factor expressed in the growth and synthetic phases of the cell cycle. Aims and Objectives: The aims of the study were to analyze CDX2 expression and Ki-67 labeling index in different histological types of gastric carcinomas and their relationship with the patients' clinicopathological parameters. Materials and Methods: A total of 50 gastric carcinoma cases were evaluated histologically and phenotypically, along with assessment of CDX2 expression and Ki-67 labeling index. Gastric carcinomas were grouped into intestinal and diffuse types, according to Lauren classification. A semiquantitative microscopic evaluation of CDX2 expression and Ki-67 labeling index was performed and correlated with the patients' clinicopathological parameters. Results: Increased CDX2 expression correlated with higher proportion of intestinal type gastric carcinomas and a lower proportion of lymph node metastasis, lymphovascular and perineural invasion. On the other hand, high Ki-67 labeling index was found in high grade tumors with lymphovascular invasion. Conclusions: The results of our study suggest that CDX2 might be a useful marker in predicting the prognosis of patients with gastric carcinoma. Accordingly, Ki-67 index seems to be useful in identifying a group of patients with aggressive tumors.
Keywords: Adenocarcinoma; CDX2; gastric carcinoma; Ki-67